CG223, a novel BET inhibitor, exerts TGF-β1-mediated antifibrotic effects in a murine model of bleomycin-induced pulmonary fibrosis. (October 2021) - Kaneshita, Shunya; Kida, Takashi; Yoshioka, Makoto; Nishioka, Keisuke; Raje, Mithun; Sakashita, Aki; Hirano, Aiko; Sagawa, Tomoya; Kasahara, Akiko; Inoue, Takuya; Fujioka, Kazuki; Nagahara, Hidetake; et al.
Abstract: Pulmonary fibrosis is a progressive disease with poor prognosis and limited therapeutic options. In this study, we evaluated the potential therapeutic effects of CG223, a novel inhibitor of bromodomain and extra-terminal motif (BET) proteins, on pulmonary fibrosis by focusing on the transforming growth factor-β1 (TGF-β1) pathway. In a murine model of bleomycin-induced pulmonary fibrosis, CG223 attenuated fibrosis while reducing the infiltration of inflammatory cells into the lungs. Fibroblasts expressing BRD4, a member of the BET protein family, were enriched in the tissue regions corresponding to bleomycin-induced fibrotic lesions. Additionally, pulmonary fibroblasts isolated from bleomycin-instilled mice showed a significantly increased association of BRD4 with the promoters of two pro-fibrotic genes linked to the entry into the TGF-β1 autocrine/paracrine loop, thrombospondin 1 ( Thbs1 ) and integrin β3 ( Itgb3 ), as well as with the promoter of a myofibroblast marker gene, actin alpha 2 ( Acta2 ). Subsequent in vitro studies with murine primary lung fibroblasts showed that the mRNA induction of Thbs1, Itgb3, and Acta2 by TGF-β1 can be inhibited by CG223 in a dose-dependent manner. Taken together, CG223-induced BRD4 inhibition suppressed lung fibrogenesis by affecting multiple genes, including those involved in the triggering of the TGF-β1 autocrine/paracrine loop.